2007
DOI: 10.1002/eat.20369
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of eating disorders: A systematic review of the literature

Abstract: The strength of the bodies of literature was moderate for factors associated with AN and BN outcomes and weak for BED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
337
0
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(378 citation statements)
references
References 76 publications
(138 reference statements)
15
337
0
26
Order By: Relevance
“…The total score is utilized to determine the overall level and stage of RFC (Pre-Contemplation, Contemplation, Preparation, Action, or Maintenance). The total score ranges from 20-100 and the individual stage of change score ranges are: Pre-contemplation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), Contemplation (30-49), Preparation (50-69), Action (70-89), and Maintenance (90-100). The instrument has demonstrated good internal consistency (0.90) and test-retest reliability (0.89).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score is utilized to determine the overall level and stage of RFC (Pre-Contemplation, Contemplation, Preparation, Action, or Maintenance). The total score ranges from 20-100 and the individual stage of change score ranges are: Pre-contemplation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), Contemplation (30-49), Preparation (50-69), Action (70-89), and Maintenance (90-100). The instrument has demonstrated good internal consistency (0.90) and test-retest reliability (0.89).…”
Section: Methodsmentioning
confidence: 99%
“…Many of the difficulties plaguing research on the course of illness and recovery from AN are due to the immature qualifications and definitions of outcomes. [24][25][26] There are practical implications that stem from such poor definitions. Ambiguous recovery objectives can result in untimely discharge from treatment and poor outcomes.…”
Section: Outcomes Of Anorexia Nervosamentioning
confidence: 99%
“…AN has the highest mortality rate of any psychiatric disorder (Keel et al, 2003;Sullivan, 1995) and is associated with numerous psychological problems, including depression, anxiety, and suicide (Berkman, Lohr, & Bulik, 2007;Birmingham, Su, Hylinsky, Goldner, & Gao, 2005). Yet many questions about the etiology of AN remain (Chavez & Insel, 2007;Stice, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Markowtiz et al (2015) found that the rate of dropout for prolonged exposure therapy was nine times higher among patients with comorbid PTSD and major depressive disorder than in non-depressed patients. Notably, the impact of depression on outcome in PTSD treatment is similar in other disorders, where co-occurring depression has been shown to negatively impact the course of treatment and outcome for social anxiety disorder (Chambless, Tran, & Glass, 1997; Erwin, Heimberg, Juster, & Mindlin, 2002), obsessive–compulsive disorder (Abramowitz, 2004), and eating disorders (Berkman, Lohr, & Bulik, 2007; Löwe et al, 2001). …”
Section: Introductionmentioning
confidence: 91%